(untitled) - Ereshefsky, Marc (Cambridge, U.K., 2001)
Invented before the introduction of evolutionary theory, Linnaeus's system of classifying organisms is based on outdated theoretical assumptions, and is thought to be unable to provide accurate biological classifications. Marc Ereshefsky argues that biologists should abandon the Linnaean system and adopt an alternative that is more in line with evolutionary theory. He traces the evolution of the Linnaean hierarchy from its introduction to the present. He illustrates how the continued use of this system hampers our ability to classify the organic world, and then goes on to make specific recommendations for a post-Linnaean method of classification. Accessible to a wide range of readers by providing introductory chapters to the philosophy of classification and the taxonomy of biology, the book will interest both scholars and students of biology and the philosophy of science.
Keywords: Biology,Sinh học; Classification,Philosophy,Phân loại,Triết lý